From Policy to Practice: Supporting Healthier Childcare Environments - Tillery, Hannah (My University, 2025)
The Douglas County Healthy Childcare Project aimed to improve the health and well-being of young children by supporting licensed childcare providers in implementing evidence-based wellness policies. As Project Coordinator, I led the development, implementation, and evaluation of five key policies focused on aligning meals with the Child and Adult Care Food Program (CACFP) meal pattern, promoting and supporting breastfeeding mothers, limiting screen time, promoting 60–90 minutes of daily physical activity, and creating tobacco-free environments that address third hand smoke exposure. Through collaborative policy reviews, tailored technical assistance, and resource development, I worked directly with childcare providers to assess current practices, co-develop realistic policy updates, and support implementation efforts. I created a resource guidebook and companion posters to inspire and sustain policy adoption, providing clear, actionable strategies for a range of childcare settings. Program monitoring included the review of updated handbooks and provider-submitted documentation, ensuring long-term accountability and alignment with public health standards. This project translates academic training into real-world impact, demonstrating how targeted policy interventions in early care and education settings can address health disparities and foster lifelong healthy habits. It also highlights the importance of environmental context, community engagement, and resource accessibility in driving sustainable health improvements.
Keywords: childcare policy; early childhoold health; health promotion; public health implementation; policy adoption; community-based intervention